IMPLEMENTASI PELAYANAN PUSAT PEMBELAJARAN KELUARGA (PUSPAGA) PROJOTAMANSARI DI KABUPATEN BANTUL DALAM PENCEGAHAN KEKERASAN PADA ANAK - Maska Septafiya Angesti; Fauzian Nur Azizah (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2023)
The problem of violence against children is a problem that still occurs in community life, including in Bantul Regency. Pusat Pembelajaran Keluarga or PUSPAGA is a service unit that plays a role in fulfilling and protecting children's rights, such as preventing violence against children. This research aims to determine the implementation of public services in PUSPAGA Projotamansari, Bantul Regency in preventing violence against children. The research was conducted using a qualitative approach with descriptive methods. Data collection was carried out using interview and observation methods. Interviews and observations are based on indicators of the PUSPAGA implementation assessment instrument from Kementerian Pemberdayaan Perempuan dan Perlindungan Anak, which consists of Institutions, Resources, Activity Programs/Services, Service Protocols for COVID-19 mitigation, as well as Monitoring, Evaluation, and Reporting. Then, the results of the interview were scored and analyzed descriptively. Based on the research results, only two of the five indicators fill the assessment standards, namely institutions and resources. PUSPAGA Projotamansari Bantul Regency's public services in preventing violence against children are not yet optimal because the available facilities are not yet complete, information regarding PUSPAGA is not yet known to all the community, causing a lack of community participation, and the services provided do not meet standard quality. Therefore, it is necessary to fulfill completeness and increase resources, increase socialization of PUSPAGA services, as well as improve the quality and range of services at PUSPAGA Projotamansari.